A Construction of Multisender Authentication Codes with Sequential Model from Symplectic Geometry over Finite Fields. (30th April 2014) - Chen, Shangdi; Yang, Chunli
Abstract : Multisender authentication codes allow a group of senders to construct an authenticated message for a receiver such that the receiver can verify authenticity of the received message. In this paper, we construct multisender authentication codes with sequential model from symplectic geometry over finite fields, and the parameters and the maximum probabilities of deceptions are also calculated.